2008
DOI: 10.1089/bfm.2007.0022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Manual and Electric Breast Pumps Among WIC Women Returning to Work or School in Hawaii

Abstract: Our findings suggest that the manual breast pump may work as well as the electric breast pump when breastfeeding is encouraged and supported among women returning to work or school full-time. Particular attention should be given to examining reasons why women with greater education breastfed for a shorter duration. Further research is needed to validate these results to better inform breastfeeding women returning to work or school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…Sixteen full reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in the review. Two conference abstracts were excluded because of their limited information.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen full reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in the review. Two conference abstracts were excluded because of their limited information.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic data varied in quantity and in categorization, making comparisons across studies difficult. The mean age of participants varied between 16.2 and 31.6 years, and studies tended to focus on women of specific ethnicity, such as white, 21,24,25,28,31 black, 19,22,32 Hawaiian, 23 or Hmong. 27 In 5 of the 6 studies that reported relationship status, the majority of participants were married or living with their partner.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations